DDCC based all-pass filters using minimum number of passive elements - Metin, B.; Cicekoglu, O.; Pal, K. (2007 50th Midwest Symposium on Circuits and Systems, 2007)
In this study, three first order all-pass filters are proposed using differential difference current conveyor (DDCC), a capacitor and a resistor without element-matching restriction. The theoretical results are verified with SPICE simulations.